Service Quality on Customer Satisfaction and Its Impact on Customer Loyalty at KFC in South and Southeast Asia - Lin, Dr. Jocelyn Lee Jia; Ling, Dr. Hui Lim; Liem, Dr. Gai Sin; Batul, Ms. Atiba; Binti Shamsudin, Nur Adnin Shazlyana; Binti Zainal Abidin, Nur Afifah; Bt. Mohd. Farid, Nur Aina Arisya; Binti Mohd. Shuhaimi, Nur Alya Umairah; Kurniawan, Egananda; Dutta, Deepjyoti; Hasani, Bhavesh K. (AIBPM Publisher, 2023)
Kentucky Fried Chicken (KFC) is the world’s well-known global brand of fast food that has more than 26,000 restaurants in over 150 countries and territories around the world. Due to Its cheapness, quickness, and convenience, it has always become a global favorite meal for many people. However, the quality of services also plays an important role in KFC’s success as they apply customer-oriented services. Their empathy and reliability towards their products and services give many reviews on the internet. Although there are many top brands in the fast-food industry, KFC has succeeded in quickly developing its business as they are constantly expanding throughout the world. Therefore, their success raises an issue of how they maintain their customer’s loyalty. To better understand this research, an online survey has been created to collect the data needed. This survey involves 100 participants from Malaysia, Indonesia, and India through a questionnaire in a Google Form. The quantitative method was used with random sampling. The data were utilized with the regression test, one sample t-test, and f-test. Based on the findings, KFC's service quality has a favorable impact on customer loyalty in each country.